1997
DOI: 10.1149/1.1837721
|View full text |Cite
|
Sign up to set email alerts
|

On‐Line FTIR Spectroscopic Investigations of Methanol Oxidation in a Direct Methanol Fuel Cell

Abstract: A real-time Fourier transform infrared spectroscopy (FTIRS) analysis of the products of methanol oxidation in a prototype direct-methanol fuel cell operating at high temperatures (150 to 185°C) is reported here. The methanol oxidation products on platinum black and platinum-ruthenium catalyst surfaces were determined as a function of the fuel cell operating temperature, current density, and methanol/water mole ratio. Neither formaldehyde nor formic acid was detected in anode exhaust gas at all cell operating c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
2
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(80 citation statements)
references
References 2 publications
1
74
2
3
Order By: Relevance
“…This reaction can be considered as a model reaction for the electrooxidation of small organic molecules. In addition, it is also of technical interest, as formic acid is a reaction intermediate in direct methanol fuel cells [6] and was also proposed as a fuel for lowtemperature fuel cells. [7] It is generally accepted that the reaction proceeds through two different reaction pathways ("dual-path mechanism"): an "indirect" pathway involving formic acid dehydrogenation and subsequent electrooxidation of the resulting adsorbed CO to CO 2 , and a "direct" pathway, which proceeds directly, without CO ad formation, to CO 2 .…”
mentioning
confidence: 99%
“…This reaction can be considered as a model reaction for the electrooxidation of small organic molecules. In addition, it is also of technical interest, as formic acid is a reaction intermediate in direct methanol fuel cells [6] and was also proposed as a fuel for lowtemperature fuel cells. [7] It is generally accepted that the reaction proceeds through two different reaction pathways ("dual-path mechanism"): an "indirect" pathway involving formic acid dehydrogenation and subsequent electrooxidation of the resulting adsorbed CO to CO 2 , and a "direct" pathway, which proceeds directly, without CO ad formation, to CO 2 .…”
mentioning
confidence: 99%
“…For the MEA tested at 180 ºC, the value for the high frequencies resistance increased sharply during the three synthetic reformate cycles when compared to first three cycles MEAs 1-3. High temperature DMFC studies, based on a phosphoric acid PBI MEAs, showed that an increase in the operating temperature improves the kinetics of the methanol oxidation and induces a shift of electrochemical selectivity toward complete oxidation of methanol to CO 2 , reducing the formation of intermediates [3].…”
Section: Eismentioning
confidence: 99%
“…A high temperature DMFC was first studied in the 1990's using phosphoric acid doped PBI as electrolytes [3][4][5]. The assembled DMFC reached a maximum of 0.1 W·cm -2 , at 200 °C [4].…”
Section: Introductionmentioning
confidence: 99%
“…A banda em 1739 cm -1 se inicia em 0,70 V e pode ser atribuída ao estiramento da ligação C=O de um grupo carbonil proveniente de um aldeído (-CHO) e/ou de um ácido carboxílico (-COOH) (BRON e HOLZE, 2000;LIMA et al, 2003;VIGIER et al, 2004), já que é muito difícil especificar a procedência deste grupo, uma vez que a banda C=O para um grupo ácido e para um aldeído estão separadas por cerca de (CHANG et al, 1990;LI et al, 1997;SOUZA et al, 2002;LIMA et al, 2003 SMITH et al, 1999;XIA, 1999), uma vez que os átomos de Sn promovem um aumento na distância entre os sítios ativos de Pt, dificultando assim a adsorção de CO na configuração em ponte.…”
Section: Espectroscopia No Infravermelho Com Transformada De Fourier unclassified
“…Desta forma, sugere-se que a produção de CO 2 não se deve apenas a oxidação de CO ads , podendo ocorrer também a partir da oxidação sucessiva dos intermediários reacionais oriundos da eletrooxidação do glicerol. , esta banda é detectável em torno de 1,20 V e corresponde a deformação assimétrica da molécula de CO 2 (CHANG et al, 1990;LI et al, 1997;SOUZA et al, 2002;LIMA et al, 2003). Em 1645 cm , que se forma a partir de 0,90 V no Au e 1,00 V no AuSn, indica a formação espécies intermediárias contendo grupamentos carbonil (C=O), provavelmente proveniente de aldeídos e/ou ácidos carboxílicos (BRON e HOLZE, 2000;LIMA et al, 2003;VIGIER et al, 2004).…”
Section: Espectroscopia No Infravermelho Com Transformada De Fourier unclassified